EFFORTS TO STRENGTHEN MENTAL ENTREPRENEURS THROUGH ONLINE BASED DIGITAL MARKETING TRAINING FOR YOUTH OF PRODUCTIVE AGE - Nandang Rukanda; Rina Kaniati; Cucu Samsudin (IKIP Siliwangi Bandung, 2021)
This research has the objectives to be achieved, namely, (1) To describe the whole picture of the state of society in entering the industrial era 4.0, its relevance to the mastery and use of social media which has become a primary need and daily culture, (2) To determine the process of implementing training Online-based digital marketing for youths of productive age carried out by the SAE Cipta Mandiri West Bandung Regency Course and Training Institute and (3) To find out the results of online-based digital marketing training. This research uses a qualitative approach and descriptive methods. The research subjects consisted of one manager, two resource persons and 3 participants. Data collection techniques used (1) Observation, (2) Interviews and (3) Documentation Studies. Data analysis was carried out by looking for similarities and differences from the collected data. The theoretical basis used is the concept of community empowerment, the concept of training, entrepreneurship and digital marketing. The results showed that modernization also influenced the development of aspects of life in the Sundanese community. Entering the era of the 4.0 generation industrial revolution, people are more intensively interacting with digital and virtual systems. Online-based digital marketing training works effectively with participatory andragogical methods and the results can improve cognitive, affective and psychomotor domains in digital marketing skills.